Turnover intention; predicting age role on perceived work exhaustion in hospitality industry / Irina Mohd Akhir ... [et al.] - Mohd Akhir, Irina; Rozekhi, Nor Azureen; Rani, Zaharah; Zakaria, Nurul’Aishah @ N; Abd Hakim, Fairuz; Johari, Noorsa Riza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Hospitality provider needs to be well motivated to ensure high level of service delivery and outstand competitors. Nevertheless, due to the nature of work in hospitality service industry, they exposed to higher degree of work exhaustion and faced a great challenge to remain in the industry. In many work exhaustion models, work load causes work exhaustion. Increase in work exhaustion can only scarce the number of hospitality provider that continuesly feel motivated and resulting turnover issue. Extremes of activity and work in nature, demands constant energy to remain focused, which can lead to exhaustion. Past research proposed that different age have different abilities including handling emotions during service encounter (Emotional Intelligent), and the physical ability coping with extreme tasks. Therefore an exploration study on age variable role within this challenging hospitality context is emphasize on. The perceived work exhaustion is explored within different level of age in the hospitality entertainment work context, due to extremes of activities in workload, and time pressure during service encounter, in line with Mediation-Conceptual Model by Moore (2005). This study aim on outlining the role of age, not just as work exhaustion’s indicator, but to explore the propose role as mediator on the relationship of perceived work exhaust and turnover intentions. Past studies however, only explores work exhaustion in less demand work nature (hotel industry). Thus, it is acculcable worth to bring attention to the variables due to the inconclusive of the similar study within hospitality-entertainment industry, prospecting the study into amusement park context. This study applying secondary data through scrutiniting past research. Looking into future study of exploratory and quantitative, utilizing closed-ended questionaire adapting items crutial to the study objectives. The discovery of identified age roles then anticipated to assist the mediating variables’ controlling strategies. Expecting the hospitality provider’s well being in the rapidly challenging field, and ease turnover issues. Consequently hospitality job stays relevent in the field.